HUBUNGAN SIKAP IBU TENTANG PIJAT BAYI DENGAN PERILAKU IBU DALAM MEMIJAT BAYI DI POSYANDU WILAYAH KERJA PUSKESMAS KESAMBEN KABUPATEN JOMBANG - Ardiyanti Hidayah; Najah Soraya Niah; Miftahus Shomad (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2023)
Introduction: Massage is a method of healing or traditional health therapy, by applying pressure to the body, either in a structured, unstructured, sedentary or moving place by applying pressure, movement or vibration, either done manually or using a mechanical device. Massage can be done at all ages including babies. Touch and massage the baby after birth can provide assurance that there is continuous body contact that can maintain a feeling of security in the baby. Based on a preliminary study conducted at the Posyandu in the working area of the Kesamben Health Center, Jombang Regency. Information obtained from several officers at the Posyandu, that mothers who visited the Posyandu had received information about the benefits of infant massage, but in reality, there are still many mothers who do not want to massage their babies. Objective: The aim of the study was to determine the relationship between the mother's attitude towards infant massage and the behavior of infant massage at the Posyandu in the working area of the Kesamben Health Center, Jombang Regency. Methods: This type of research is a type of descriptive quantitative research. Data collection for the variable attitude towards baby massage and the variable behavior of massaging the baby were collected by means of a questionnaire. The population in this study were all mothers who had babies 0-11 months who lived in the Working Area of the Kesamben Health Center, Jombang Regency in 2023 with a sample of 68 samples. The sampling technique is purposive sampling. Data analysis was carried out using univariate and bivariate methods. Results: The results showed that the value of P = 0.002, this value is smaller than α = 0.05, thus there is a relationship between attitudes towards infant massage and massaging behavior or the hypothesis (Ha) is accepted. Conclusion: From the results of this study it is hoped that the posyandu in the working area of the puskesmas will open a baby massage class for mothers so that mothers are motivated to do baby massage themselves.